P024 CROHN'S DISEASE MESSAGING ON TWITTER: WHO'S TALKING?. (18th January 2018) - Rowe, Anthony; Rowe, Samantha; Silverman, Anna; Borum, Marie L
Abstract: Twitter, a popular social networking service, enables users to interact with messages (tweets) limited to 140 characters. It is an increasingly powerful mechanism to convey information. There is limited data on the use of Twitter for disseminating medical information. This study evaluated the utilization of Twitter for Crohn's disease messaging. Social Feed Manager (SFM; version 1.10.0; GW University, 2017), a software that can query social media platforms, queried Twitter's application programming interface to collect user information, origin, and frequency of messaging about Crohn's during a 10 day period. SFM queried Twitter using the terms #IBD, #Crohns, #crohnsdisease, #crones, #chrons, #chronsdisease, and #cronesdisease. The collection was limited by Twitter's determination relevance, allowable timeframe collection, and user's misspelling of disease condition. 3810 tweets were collected. The elimination of retweeted messages resulted in 2030 unique tweets. There were 133 different users, of which 24.4% were patients, 20.5% foundations, and 19.2% physicians (Chart 1). In users who enabled geotagging, there were 9 countries of origin with 45.1% United Kingdom, 37.7% United States and 9% Canada. 145 tweets were resent (133 retweeted 2–24, 6 retweeted 25–49, 4 retweeted 50–99, 2 retweeted >100 times) with the initial message originating from foundations (32.1%), physicians (19.7%), IBD patients (14.6%) (Graph 2). Twitter's platform can be used for dissemination of unfiltered medical information messaging by diverse worldwide users. It is important that physicians are aware of information sources that are utilized by individuals with Crohn's disease. Additional study to analyze messaging content will improve the understanding the role that Twitter may have in providing medical information.